Carbon Nanotube Integration with a CMOS Process - Perez, Maximiliano Sebastian (2010)
This work shows the integration of a sensor based on carbon nanotubes using CMOS technology. A chip sensor (CS) was designed and manufactured using a 0.30 μm CMOS process, leaving a free window on the passivation layer that allowed the deposition of SWCNTs over the electrodes. We successfully investigated with the CS the effect of humidity and temperature on the electrical transport properties of SWCNTs. The possibility of a large scale integration of SWCNTs with CMOS process opens a new route in the design of more efficient, low cost sensors with high reproducibility in their manufacture.